Economic growth and performance in Latin America - Hofman, André A. (ECLAC SantiagoCL, 2000)
Addresses some important questions with respect to economic growth in Latin America, comparing the so-called post-crisis period and the 1990s with a base period in a selected group of nine countries (Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Jamaica, Mexico and Peru). Focuses on the relation between the structural reforms applied in the region in the last decade, which have led to a change in the Latin American development model, and their impact on economic growth, equity and employment.